Two new oribatid mites from Costa Rica, Mixacarus turialbaiensis sp. n. and paulianacarus costaricensis sp. n. (Acari, oribatida, lohmanniidae) - Fernández, Néstor Alfredo (2017)
In this paper we describe two new species belonging to the family Lohmanniidae: Mixacarus turialbaiensis sp. n. and Paulianacarus costaricensis sp. n. from Costa Rica.